Multi-Aircraft Environmentally-Scored Weather-Resilient Optimised 4D-Trajectories - Dungen, N.H.M. van den; Sutopo, N.D.K.; Prats, X.; Di Vito, V.; Riccio, A. (Netherlands Aerospace Centre NLR, 2021)
Weather phenomena are one of the biggest causes for significant delays and unpredictable disruptions within air traffic management (ATM) network operations. The changing global climate increases the future severity and frequency of these air traffic disturbing weather phenomena. This deteriorates the predictability of 4D trajectory ATM network planning and potentially increases the delays within air traffic operations. Furthermore, aviation itself has a responsibility to mitigate its climate impact to improve the long-term sustainability of the ATM operations and to contribute to the global effort towards the reduction of anthropogenic climate change. The SESAR2020 exploratory research project CREATE (Grant 890898) aims to find answers on how to improve the weather-resilience of ATM-operations and to reduce its climate impact. A concept of operations (ConOps) has been developed which describes an integrated trajectory optimisation framework to tactically define environmentally-scored optimised 4D trajectories, for a multi-aircraft airspace configuration, using advanced numerical weather prediction models, combined with air traffic control (ATC) driven demand-capacity balancing methods. The framework will be applied to an en-route use-case focusing on the unorganised traffic over the North Atlantic, and a Terminal Manoevring Area (TMA) use-case focusing on the Naples Capodichino airspace. The optimised trajectories aim to evade thunderstorms and contrail formation regions, whilst minimising CO2, non-CO2 and local air quality (LAQ) impacts.
This report is based on a presentation to be held at FABEC / InterFAB Research Workshop, "Climate change and the role of air traffic control", 22-23 September 2021 in Vilnius / Lithuania.